High Life : Condo Living in the Suburban Century. - Lasner, Matthew (New Haven : Yale University Press, 2012)
The first comprehensive architectural and cultural history of condominium and cooperative housing in twentieth-century America.
Cover -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgments -- Introduction: Collective Homeownership -- Chapter 1 The Browne Decades -- Chapter 2 Town & Country -- Chapter 3 Cooperative Commonwealth -- Chapter 4 Vertical Subdivisions -- Chapter 5 Leisure Worlds -- Chapter 6 California Townhouses -- Chapter 7 Back to the City -- Epilogue -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- S -- T -- U -- V -- W -- Y -- Z -- Illustration Credits
Description based upon print version of record.
JSTOR
Keywords: Condominiums -- United States; Apartment houses, Cooperative -- United States; Immeubles d'habitation coopératifs -- États-Unis.; ARCHITECTURE / Criticism; Apartment houses, Cooperative; Condominiums; United States